8. EVALUATION OF THE RELATIONSHIP BETWEEN SYMPTOMS AND FACTORS ASSOCIATED WITH GASTRIC COLLATERAL BLOOD STASIS SYNDROME IN PATIENTS WITH CHRONIC ATROPHIC GASTRITIS (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the clinical characteristics and associated factors of Gastric Collateral Blood Stasis syndrome in patients with chronic atrophic gastritis.Subjects and methods: A cross-sectional descriptive study was conducted involving 400 patients diagnosed with chronic atrophic gastritis at two branches of the University Medical Center Ho Chi Minh city.Results: The Gastric Collateral Blood Stasis syndrome pattern accounted for 19% of cases. Symptoms including abdominal distension, fixed epigastric pain, pressure-sensitive epigastric pain, dark facial complexion, dark red tongue, sublingual blood stasis, and wiry pulse showed statistically significant differences when compared to other syndromes (p < 0.05). Meanwhile, symptoms such as melena, petechiae on the tongue, and choppy pulse did not differ significantly between syndrome groups (p > 0.05).Conclusion: Factors such as gender, history of Helicobacter pylori infection, and specific clinical symptoms demonstrated statistical significance in the diagnosis of Gastric Collateral Blood Stasis syndrome.
Keywords: Chronic atrophic gastritis, Gastric Collateral Blood Stasis syndrome, traditional medicine.